How do Physicians Decide to Refer Their Patients for Psychiatric Genetic Counseling? A Qualitative Study of Physicians' Practice. Issue 6 (17th May 2016) - Leach, Emma; Morris, Emily; White, Hannah J.; Inglis, Angela; Lehman, Anna; Austin, Jehannine
Abstract: Psychiatric genetic counseling (PGC) is an emerging specialty discipline within the genetic counseling profession. A specialist PGC service was founded in 2012 in Vancouver, Canada, and though patient benefits have been demonstrated, many physicians do not regularly refer patients to the service despite awareness of its availability. We conducted a qualitative study involving semi‐structured telephone interviews with Vancouver‐based physicians who were aware of the PGC service to explore this phenomenon. Interviews were audio‐recorded, transcribed verbatim, coded, and analysed for emergent themes. Consistent with a grounded theory approach, constant comparison was employed throughout data collection and analysis. Analyses of interviews conducted with 12 physicians revealed that referral practices were informed by perceptions about the purpose of PGC and interpretation of patient cues. Physicians perceived PGC as an information‐focused intervention, and considered referral when patients explicitly expressed desire for information about recurrence risk or etiology that they felt unable to adequately address themselves. Even when physicians identified psychotherapeutic benefits of PGC, patient needs of this nature were not perceived as cues prompting referral to PGC. These data suggest that further work is necessary to position PGC in physicians' minds as a service that could potentially benefit most individuals with psychiatric disorders and their families, and that it encompasses more than information provision. It is important to increase physicians' awareness of the complementary role that genetic counselors can play to that of the physician in providing psychotherapeutically oriented counselling about illness etiology.